Association between ischemic stroke and hyperintense plaques detected by high-resolution vessel wall MRI in Japanese patients with intracranial atherosclerotic disease - Naoki Takayama; Takakuni Maki; Yasutaka Fushimi; Masakazu Okawa; Yohei Mineharu; Kiyofumi Yamada; Kiyofumi Yamada; Tao Yang; Yu Yamamoto; Keita Suzuki; Ken Yasuda; John Grinstead; et al. (Frontiers in Stroke)
BackgroundConventional MRI sequences are insufficient for the detailed depiction of intracranial atherosclerotic disease (ICAD) plaques. The aim of this study was to investigate the association between ischemic events and intracranial atherosclerotic plaque characteristics using a high-resolution T1-weighted black-blood MRI technique (DANTE T1-SPACE) in the anterior circulation in the Japanese population.MethodsPatients with a total of 108 lesions causing ≥40% stenosis on the C1–5 segments of the intracranial internal carotid artery (ICA) or M1 segment of the middle cerebral artery (MCA) were included. Hyperintense plaques (HIPs) were defined as plaques with a spot of signal intensity (SI) higher than 1.5-fold SI of the ipsilateral temporal muscle on DANTE T1-SPACE. The vessel wall lesions were divided into symptomatic and asymptomatic groups. The lesions in the symptomatic group were classified as artery-to-artery embolism, hemodynamic infarction, cardiac embolism, undetermined and transient ischemic attack (TIA).ResultsAmong the 108 plaques, 19 were symptomatic and 89 were asymptomatic. The percentage of HIPs in the symptomatic group was significantly higher than in the asymptomatic group (57.9% vs. 24.7%, p = 0.01). In the symptomatic group, the proportion of HIPs in the A-to-A embolism subgroup was higher than in the other subgroups.ConclusionsDANTE T1-SPACE may aid in the identification of intracranial plaques with imaging characteristics suggestive of increased stroke risk, particularly hyperintensity potentially reflecting intraplaque hemorrhage.